LEGAL PROTECTION FULFILLMENT OF PATIENT RIGHTS TO THE IMPLEMENTATION OF INFORMED CONSENT IN SECTIO CAESARRIAN PATIENT - OK Isnainul; Ronal Hasudungan Sianturi; Nurhasmi Nurhasmi (International Journal of Latin Notary, 2021)
The issue of patient rights in relation to medical decisions is an important consideration that often does not receive much attention. The law has long recognized the right of individuals to self-determination. The core part of these rights is the right to accept or refuse medical treatment as outlined in the informed consent. The purpose of this study is to analyze: 1) the rights of sectio caesarea patients in Informed Consent, 2) legal responsibility for the absence of informed consent in sectio caesarea patients, 3) legal protection of sectio caesarea patient. This type of research is using normative juridical research and empirical juridical research. Data analysis in this study is inductive. The results of the legal study of this study were obtained: 1) Sectio caesarea patients' rights in informed consent are seen when the patient is given sufficient information about his treatment in terms of diagnosis and medical procedures, the purpose of the medical action taken, other alternative actions and risks, complications that may occur, the prognosis of the action taken, including the benefits. and disadvantages of each alternative therapy and can be expanded with additional information so that the patient participates appropriately in the effort to cure the disease; 2) Legal responsibility for the absence of informed consent in sectio caesarea patients is that doctors who take medical actions can be equated with acts of negligence so that they can be punished according to the applicable laws and regulations; 3) In general, patients are protected by the Law of the Republic of Indonesia Number: 29 of 2004 concerning Medical Practice and Law of the Republic of Indonesia Number: 36 of 2009 concerning Health. Normatively, patients must be treated in accordance with these provisions, patients must be treated as subjects who have a major influence on service outcomes and not just objects. Negligence of medical personnel must be normative and not physically or psychologically because it will be difficult to know the real inner state of the sectio caesarea patient.